The Duel for France, 1944 - Blumenson, Martin (Boston Houghton Mifflin, 1963)
Strategic history of the clash between German and Allied forces in Normandy during World War 2.
Include Pictures and Index
Keywords: World War (1939-1945) -- German Occupation, 1940-1945 -- Military Campaigns